Gerações em conflito: a juventude contemporânea entre o passado e o presente - Birolli, Maria Izabel de Azevedo Marques (2016)
The thesis is a study on the current youth, more specifically about the generational gap experienced by young people, with the object of study the Jornadas de Junho de 2013 (June 2013 Journey) in Brazil. My hypothesis is that the generations of young people who which command the many street manifestations and in digital networks are experiencing another moment of "revolt", but also reveals some signs of political experiences of the '60s generation, which return to the youth movements, where many of them were born update and reinterpreted, as is the case of environmentalism, feminism, the struggles against racism and the problem of representation in politics. The June 2013 Journey and its consequences were also understood as a social explosion of a social resentment, accumulated frustrations of past generations that gave rise recently to a polarization in the common sense of politics in Brazil. This polarization also affects youth with its striking presence, if no defining in today's conflicts in the networks, on the streets and in recent ideological debates, presented as two ideal types: a generation "neoconservative" and other "naturalistic"